Questions of perception in Elizabeth Bishop’s poetry - Gonçalves Júnior, Marcelo de Carvalho (2023)
This dissertation analyses the particular method in which the American poet Elizabeth Bishop perceives both the external and internal world through her poetry. Before going to the poems themselves, we first look into the ways Elizabeth Bishop has been traditionally read by the critics – either as a poet of objectivity and impersonality or a poet of subjectivity and autobiography – and how this dichotomy hurts our understanding of her work by isolating only one particular aspect of it in detriment of the other. After exploring this debate, we propose a new way of reading Bishop, examining how objectivity and subjectivity, as they appear in her work, are not mutually exclusive or that one of them is not predominant overall. In order to deepen our understanding of her work, we close read a number of her most celebrated poems, while also establishing parallels between her poetry and the phenomenology of Maurice Merleau-Ponty. The first chapter is dedicated to exploring the relationship between Elizabeth Bishop and the external world, while the second explores how her poetry relates to the internal one. Despite the way in which the chapters are divided, in Bishop's poetry the external and internal are more linked than one might assume – there is no need to choose to read her as either an external or internal poet in absolute. Finally, we analyze how Bishop is able to demonstrate her subjectivity in the world as she perceives it and how said subjectivity is worked through the poem itself, and not only in relation to autobiographical matters